COMPARISON OF FRASERING BETWEEN CHARLES CHING AND INGGRID PATRICIA IN THE COMPOSITION OF SETITIK EMBUN BY MOCHTAR EMBUT - Siyunita, Nadya Primeswari; Suryandoko, Welly (Solah, 2025)
Setitik Embun is one of the many works of Mochtar Embut which is very popular among the public. Setitik Embun is a vocal composition in the style of seriosa music. This study aims to describe the vocal technique in the composition and describe the obstacles when playing the work. This study is a qualitative descriptive study. Data collection was carried out by means of observation, documentation, and interviews. Data analysis techniques were carried out qualitatively consisting of data reduction, data display, verification (conclusion). Data validation was obtained by data triangulation and observer triangulation. This study resulted in the guitar playing techniques used in the composition including; vibrato, phrasering, articulation, breathing and interpretation. The constraint factors that need to be considered in playing the composition include stage fright, nervousness, breathing and communication between the vocals and the accompaniment.